Integrating an Upgraded Constituent System in a System of Systems: A SysML Case Study. (28th October 2015) - Ingram, Claire; Fitzgerald, John; Holt, Jon; Plat, Nico
Abstract: A system of systems (SoS) relies on each constituent system contributing towards achieving some global emergent behavior. Integrating constituent systems can be particularly challenging for SoS engineering, partly because of the independence of the constituents and the difficulty of producing a realistic, scalable test environment before changes are deployed to the live environment. For this reason modeling and simulation can be important tools for regression testing within an integration scenario. We provide a worked example of an SoS integration scenario using a traffic management system as demonstrator, employing a structured, model‐based framework (the COMPASS Integration Framework) designed for integrating CSs in a variety of SoS integration scenarios. The Framework is designed to be used with architectural modelling views (we use SysML for our case study). Finally, we provide some pointers for future work and next steps.